Morphological changes in the immune system organs of piglets fed with different feed additives - Prudyus, T. Y.; Shchebentovska, O.; Salyha, Y. T.; Vorobel, M. I. (Regulatory Mechanisms in Biosystems, 2023)
Nowadays, the interest in studying the impact of feed additives on the organism of piglets during critical periods of weaning remains increasingly relevant. Feed additives containing blends of essential oils with plant extracts, preparations containing dry yeast, organic acids, pro- and prebiotics are suggested to replace growth promoters and antibiotics. This contributes to the increased productivity, survivability, immune response formation, and ensuring normal intestine morphology in piglets. Proper concentrations and timing of feed additive application aimed at maintaining a healthy intestine in piglets after weaning and improving their productivity remain equally important. This study presents the results of an experiment on the use of various feed additives for piglets before weaning and their effect on the morphology of the immune system organs.The research was conducted on piglets of the Large White breed, divided into four groups of ten individuals each. From days 7 to 28 of life, various feed additives were introduced into the main diet for each group: piglets of the control group (I) received a standard nutritionally balanced diet; piglets of group II had a supplement added to the standard diet containing a combination of live yeast of the Saccharomyces genus and a complex of 6 enzymes (proteases, cellulases, xylanases, α-amylases, β-glucanases, and phytases) at a rate of 0.5 kg per ton of feed; piglets of group III received a feed additive containing a blend of essential oils with plant extracts (Thymus vulgaris, Rosmarinus officinalis, Origanum vulgaris, Capsium extract) at a rate of 0.2 kg per ton of feed; piglets of group IV had a feed additive added to the main diet containing dry yeast and egg powder enriched with immunoglobulins at a rate of 2 kg per ton of feed. The main feed used in the experiment was provided in the form of fine granules. Histological examination of the thymus, mesenteric lymph nodes, spleen, and duodenum lymphoid formations revealed that the morphological structure of the organs was preserved in piglets of all experimental groups. The partial structure of the thymus was well defined, with a clear differentiation into cortical and medullary substances. Piglets receiving the feed additive "Activo" with a blend of essential oils from plant extracts and the feed additive "Globigen Jump Start," which includes dry yeast and egg powder enriched with immunoglobulins, demonstrated a slight increase in the thymic cortex relative area, both on days 14 and 28 of the study, and an increase in the number of plasma cells. In the spleen and lymph nodes of piglets in all experimental groups, the lymphoid tissue was predominantly represented by small and medium lymphocytes; lymphoid nodules of large size with reactive centers were observed too. Brachet staining in the lymph nodes of piglets in all experimental groups revealed plasma cells with bright eosinophilia, and large nuclei predominantly with a single nucleus. However, their quantity varied, with the highest number of plasma cells observed in piglets of group IV, which received the feed additive "Globigen Jump Start" with dry yeast and egg powder enriched with immunoglobulins. Histologically, in the piglets’ duodenum, the villi were closely packed, a small number of goblet cells were located between enterocytes, plasma cells with distinct eosinophilic cytoplasm and eccentrically placed nuclei were localized in the lymphoid nodules of the mucous membrane and in the crypt areas. Their quantity was higher in piglets of groups III and IV.